Do We Have a Match? Assessing the Role of Community in Coworking Spaces Based on a Person-Environment Fit Framework - Lashani, Eileen; Zacher, Hannes (Frontiers in Psychology, 2021)
As working arrangements become more flexible and many people work remotely, the risk of social isolation rises. Coworking spaces try to prevent this by offering not only a workplace, but also a community. Adopting a person-environment fit perspective, we examined how the congruence between workers’ needs and supplies by coworking spaces relate to job satisfaction and intent to leave. We identified five needs (i.e., community, collaboration, amenities, location, and cost), of which community was expected to be the central need. An online questionnaire was distributed among coworkers in Germany and Austria, resulting in a sample of 181 coworkers. Results showed that needs-supplies fit regarding community was related to job satisfaction and intent to leave in coworking spaces. Findings for the other needs, however, did not show that congruence is associated with outcomes. Overall, the findings highlight the importance of community fit in coworking and offer insights for workers and entrepreneurs in this area.